2020
DOI: 10.1021/acs.chemrestox.0c00049
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Halogenated Tyrosyl Compounds, an Emerging Class of Disinfection Byproducts

Abstract: Halogenated amino acids and peptides are an emerging class of disinfection byproducts (DBPs), having been detected in drinking water and in washed food products. However, the toxicological significance of these emerging DBPs remains unclear. In this study, the cytotoxicity of eight halogenated tyrosyl compounds was investigated in Chinese hamster ovary (CHO) cells using real-time cell analysis (RTCA). Dihalogenated tyrosyl compounds are more cytotoxic than their monohalogenated analogues. The cytotoxicity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 50 publications
(96 reference statements)
0
14
0
Order By: Relevance
“…The compounds ( 1 ) and ( 3 )– )10 ) were found to be variously bioactive as antibacterial, anticancer, antiparasitic, antiplasmodial, antiinflammatory, and antifouling molecules [ 59 , 60 , 61 , 62 , 63 , 64 ]. A recent study focused on identifying novel marine halogenated tyrosines, identified them as components of valviamides A−D ( 11 – 14 in Table 2 ) from the cnidarians Antipathozoanthus hickmani and Parazoanthus darwini ( Table 2 ).…”
Section: Halo-amino Acids and Halogenated Non-ribosomal Peptidesmentioning
confidence: 99%
See 2 more Smart Citations
“…The compounds ( 1 ) and ( 3 )– )10 ) were found to be variously bioactive as antibacterial, anticancer, antiparasitic, antiplasmodial, antiinflammatory, and antifouling molecules [ 59 , 60 , 61 , 62 , 63 , 64 ]. A recent study focused on identifying novel marine halogenated tyrosines, identified them as components of valviamides A−D ( 11 – 14 in Table 2 ) from the cnidarians Antipathozoanthus hickmani and Parazoanthus darwini ( Table 2 ).…”
Section: Halo-amino Acids and Halogenated Non-ribosomal Peptidesmentioning
confidence: 99%
“…It should be noted that free halogenated amino acids and halogenated peptides are increasingly found in drinking water and in washed foods [ 64 ]. These compounds cannot properly be considered to be native, although they are found dispersed in nature.…”
Section: Halo-amino Acids and Halogenated Non-ribosomal Peptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…13−16 However, aromatic I-DBPs show 50−200 times higher developmental toxicity and growth inhibition than aliphatic I-DBPs 11,17 and other known I-DBPs. 10,18 Using the precursor ion scan method, numerous aromatic I-DBPs have been detected in chloraminated waters, tap water, and cooking water. 8,9,11,18,19 For instance, aromatic I-DBPs (e.g., 2,4,6-triiodophenol and 2,6-diiodo-4-nitrophenol) were widely detected in finished drinking water samples from China with concentrations up to 31 ng L −1 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Fourth, with regard to isomers, 3-CPAcAm showed a relatively higher cytotoxicity than 2-CPAcAm; similar in the case for 3-BPAcAm in comparison to 2-BPAcAm, implying that the isomeric position might play a considerable role in affecting the cytotoxicity of HPAcAms. Thereafter, to compare with other nitrogenous aromatic halogenated DBPs, the cytotoxicity index (CTI) for HPAcAms as well as halonitrophenols, halogenated tyrosyl dipeptides, halophenylacetonitriles, and halopyrroles was determined by calculating the reciprocal of the median EC 50 value of all individual members of a single DBP category . As shown in Supporting Information Table S9, HPAcAms showed higher cytotoxicity than halogenated tyrosyl dipeptides and lower cytotoxicity than halonitrophenols, halophenylacetonitriles, and halopyrroles (it is worth noting that there is a certain difference in the cytotoxicity test methods adopted in these previous studies).…”
Section: Resultsmentioning
confidence: 99%